PERAN KINERJA KEUANGAN DALAM MEMEDIASI PENGARUH UKURAN PERUSAHAAN, STRUKTUR MODAL, DAN PERTUMBUHAN PENJUALAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BEI PERIODE 2022-2024 - Rizka Gabriella Sandy; Ida Subaida; Lita Permata Sari (Fakultas Ekonomi dan Bisnis, 2026)
The basic and chemical industry sector within manufacturing companies plays a strategic role in supporting national industrial activity because it produces various basic products used in production processes across various sectors. The purpose of this study is to analyze and test the role of financial performance in mediating the influence of company size, capital structure, and sales growth on firm value. The method used in this study is descriptive quantitative. The population in this study were manufacturing companies in the basic and chemical industry sector listed on the Indonesia Stock Exchange (IDX) in 2022-2024. Purposive sampling was the sampling technique in this study. This study used Partial Least Squares – Structural Equation Modeling (PLS-SEM). The results of the hypothesis test using the Smart PLS 3.0 statistical application indicate that company size has a negative but insignificant effect on financial performance, capital structure has a significant negative effect on financial performance, sales growth has a significant positive effect on financial performance, company size has a significant positive effect on firm value, capital structure has a negative but insignificant effect on firm value, sales growth and financial performance have a positive but insignificant effect on firm value. Financial performance negatively but insignificantly mediates the influence of firm size and capital structure on firm value. Financial performance positively but insignificantly mediates the influence of sales growth on firm value.